2010
DOI: 10.1038/emboj.2010.296
|View full text |Cite
|
Sign up to set email alerts
|

miR-301a as an NF-κB activator in pancreatic cancer cells

Abstract: NF‐κB is constitutively activated in most human pancreatic adenocarcinoma, which is a deadly malignancy with a 5‐year survival rate of about 5%. In this work, we investigate whether microRNAs (miRNAs) contribute to NF‐κB activation in pancreatic cancer. We demonstrate that miR‐301a down‐regulates NF‐κB‐repressing factor (Nkrf) and elevates NF‐κB activation. As NF‐κB promotes the transcription of miR‐301a, our results support a positive feedback loop as a mechanism for persistent NF‐κB activation, in which miR‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
221
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(232 citation statements)
references
References 47 publications
8
221
0
2
Order By: Relevance
“…Several studies have demonstrated the regulation of the NF-kB pathway by miRNAs, such as miR-301a in pancreatic cancer (Lu et al, 2011), miR-146a in human monocytes (Taganov et al, 2006) and miR-199b in ovarian cancer (Chen et al, 2008). However, little is known about the regulation of NF-kB signaling in the context of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the regulation of the NF-kB pathway by miRNAs, such as miR-301a in pancreatic cancer (Lu et al, 2011), miR-146a in human monocytes (Taganov et al, 2006) and miR-199b in ovarian cancer (Chen et al, 2008). However, little is known about the regulation of NF-kB signaling in the context of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA-301a activates NFjB by downregulating the expression of the NFjB-repressing factor gene. 87 Multiple signaling pathways, including NFjB-and miRNA-mediated ones, contribute to the genesis and maintenance of EMT phenotypic cells and cancer stem cells (CSCs). These cell type configurations are linked to drug resistance.…”
Section: Micrornas As Epigenetic Targetsmentioning
confidence: 99%
“…The method involves a published lentiviral-based miRNA genetic library that contains a large number of human miRNA minigenes [142]. To screen miRNAs that specifically target TFs of interest, we utilized luciferase constructs plus the miRNA library.…”
Section: Experimental Procedures Mirna Screenmentioning
confidence: 99%
“…c-Myc activity was measured using an E2F2-Luc reporter vector consisting of the E2F2 promotor with four distinct E-boxes, CACGTG [143]. The parental vector, pSIF [142], substituted for the miRNA construct, serves as a normalization control for miRNA expression. Rluc from pRL-TK (Promega) is used to normalize transfection efficiency and total protein synthesis.…”
Section: Experimental Procedures Mirna Screenmentioning
confidence: 99%
See 1 more Smart Citation